In-situ measurements of stratospheric ozone depletion rates in the Arctic winter 1991/1992: A Lagrangian approach - Rex, Markus; von der Gathen, Peter; Harris, N. R. P.; Lucic, D.; Knudsen, B. M.; Braathen, G. O.; Reid, S. J.; De Backer, H.; Claude, H.; Fabian, R.; Fast, H.; Gil, M.; et al. (1998)
A Lagrangian approach has been used to assess the degree of chemically induced ozone loss inthe Arctic lower stratosphere in winter 1991/1992. Trajectory calculations are used to identify airparcels probed by two ozonesondes at different points along the trajectories. A statistical analysisof the measured differences in ozone mixing ratio and the time the air parcel spent in sunlightbetween the measurements provides the chemical ozone loss. Initial results were first describedby von der Gathen et al. [1995]. Here we present a more detailed description of the technique anda more comprehensive discussion of the results. Ozone loss rates of up to 10 ppbv per sunlit hour(or 54 ppbv per day) were found inside the polar vortex on the 475 K potential temperaturesurface (about 19.5 km in altitude) at the end of January. The period of rapid ozone loss coincidesand slightly lags a period when temperatures were cold enough for type I polar stratosphericclouds to form. It is shown that the ozone loss occurs exclusively during the sunlit portions of thetrajectories. The time evolution and vertical distribution of the ozone loss rates are discussed.